Design Approach for Lateral Capacity of Dowel-Type Steel Connections in Precast Reinforced Concrete Elements - Muciaccia, Giovanni (Frontiers in Built Environment, 2021)
In precast concrete building connections play a key role. Among them and especially in industrial buildings, the ability to transfer a shear force from the beam to the column is often left to steel bars (often a single one) which act as dowels. Despite several research studies carried out in recent years, there is still a lack of agreement regarding the applicability of Eurocode 2 rules for fastening in concrete to such specific design case. More specifically, the role of the edge reinforcement and the effectiveness of multiple reinforcement layers in the proximity of the steel bar do not find a unique interpretation. The present paper aims to review existing design methods, both in codes and in literature, for such connections, aiming to propose a common interpretation of the load-transfer mechanism.